Facilities and Infrastructures’ Implications Towards Teachers' Pedagogical Content Knowledge (PCK) Welcoming Merdeka Belajar Curriculum - Isatul Hasanah; Siti Rodiah; Laila AFIFAH (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Abstract The Merdeka Belajar curriculum encourages teachers to develop Pedagogic Content Knowledge (PCK). To make learning more interesting, fun, and meaningful for students. However, facilities and infrastructure have not supported teachers to implement the Merdeka Belajar Curriculum in Elementary Schools. This study aims to (1) explain the facilities and infrastructure in the Institution, and (2) the relationship between facilities and infrastructure to the teacher’s Pedagogic Content Knowledge (PCK). This research method is descriptive using a quantitative approach. The study sample is 12 people who teach grades 1 and IV. Data collection techniques include questionnaires in the form of google Forms, observation, interviews, and documentation. Data analysis techniques are in the form of the presentation of statistical data percentages. The results of this study are (1) the facilities and infrastructure in the Institution are still inadequate to meet the Merdeka Belajar Curriculum (2) the link between facilities and infrastructure to the teacher’s Pedagogic Content Knowledge (PCK) is the use of lecture learning strategies 67%, student-centered 25%, and cooperative learning 8%. So the lack of facilities and infrastructure causes the learning teachers to attend lectures opposite to the orientation of the Merdeka Belajar Curriculum.